I still believe - Camp, Jeremy; Thomas, David, 1968 June 21- (W Publishing Group, an imprint of Thomas Nelson, 2020)
When Jeremy Camp lost his beloved wife, Melissa, just months after their wedding, the last thing he wanted to do was sing praise to God. But even as he struggled through unimaginable grief and fought to hold on to his faith, God had other plans: Pick up your guitar. I have something for you to write. Jeremy obeyed, pouring out his heart, writing about the hope that God was still there, even in his deepest grief. The song he wrote that day, “I Still Believe,” has gone on to inspire millions around the world. This is the story behind that song and the movie that was inspired by it. It<U+2019>s an inside look at Jeremy<U+2019>s life<U+2014>from his difficult childhood and teenage years to the tragic passing of Melissa and the spiritual journey that followed, which inspired some of his best-loved songs and led him, eventually, to find love again. I Still Believe is a powerful heart-wrenching book about the strength of undying love and the power of faith.